That Guy Wolf Dancing - Cantor, Judith Levin, 1928- (Book collections on Project MUSE., 2001)
Since the earliest days of the British fur trade, Jewish pioneers have made Michigan their home. Judith Levin Cantor''s Jews in Michigan captures the struggles and triumphs of Michigan''s Jews as they worked to establish farms, businesses and synagogues, sparking commercial and residential development throughout the state, and even into the far reaches of the Upper Peninsula. Cantor celebrates both urban and rural immigrants, who supplied essential goods and services to those in lumbering, mining, and automobile manufacturing. She also deals honestly with questions of anti-Semitism and prejud.